2016
DOI: 10.1073/pnas.1606479113
|View full text |Cite
|
Sign up to set email alerts
|

Temporal coding of reward-guided choice in the posterior parietal cortex

Abstract: Making a decision involves computations across distributed cortical and subcortical networks. How such distributed processing is performed remains unclear. We test how the encoding of choice in a key decision-making node, the posterior parietal cortex (PPC), depends on the temporal structure of the surrounding population activity. We recorded spiking and local field potential (LFP) activity in the PPC while two rhesus macaques performed a decision-making task. We quantified the mutual information that neurons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 72 publications
(101 reference statements)
3
24
0
Order By: Relevance
“…We found that the beta phase allowing maximal encoding of Prediction Errors was offset ~27 ms on average from the phase at which most spikes synchronized to the local fields. Such a dissociation of spike-phase and encoding-phase has been reported previously for the beta frequency band in parietal cortex, where maximal information of joint saccadic and joystick choice directions were best predicted by spike counts at ~50 degree away from the preferred beta spike phase (Hawellek et al, 2016). Such phase offsets underlying maximal encoding in parietal cortex as well as in ACC, LFC and STR in our study provide constraints on the possible circuit mechanisms that permit temporal segregation of inputs streams through phase specific oscillatory dynamics (Akam and Kullmann, 2014).…”
Section: Neuronal Mechanisms Underlying Phase-of-firing Multiplexingsupporting
confidence: 80%
See 1 more Smart Citation
“…We found that the beta phase allowing maximal encoding of Prediction Errors was offset ~27 ms on average from the phase at which most spikes synchronized to the local fields. Such a dissociation of spike-phase and encoding-phase has been reported previously for the beta frequency band in parietal cortex, where maximal information of joint saccadic and joystick choice directions were best predicted by spike counts at ~50 degree away from the preferred beta spike phase (Hawellek et al, 2016). Such phase offsets underlying maximal encoding in parietal cortex as well as in ACC, LFC and STR in our study provide constraints on the possible circuit mechanisms that permit temporal segregation of inputs streams through phase specific oscillatory dynamics (Akam and Kullmann, 2014).…”
Section: Neuronal Mechanisms Underlying Phase-of-firing Multiplexingsupporting
confidence: 80%
“…We tested this hypothesis by quantifying how much Outcome, Prediction Error, and Outcome History information is available to neurons at different phase bins relative to their mean phase. If the phase-of-firing conveys information, then differences in spike counts between conditions should vary systematically across phases, as opposed to a pure firing rate code that predicts equal information for spike counts across phase bins ( Figure 4A) (Hawellek et al, 2016;Womelsdorf et al, 2012). Figure 4B shows an example neuron exhibiting phase-of-firing coding (with spikes from ACC and beta phases from STR).…”
Section: Phase-of-firing At 10-25 Hz Encodes Outcome Prediction Erromentioning
confidence: 99%
“…As mentioned above, the ≈7-8 Hz EEG component, whose phase predicts human detection performance, is strongest over frontal areas (51). Also, spike and LFP recordings in macaque parietal cortex have recently revealed a similar theta rhythm (42,55). If such theta-rhythmic topdown influences were to be found, it will be interesting to understand how they fit with the predominantly bottom-up directed theta influences observed between visual areas (33).…”
Section: Discussionmentioning
confidence: 85%
“…The effect of astrocytes on fast waves may be due to cross-frequency coupling, a mechanism whereby global slow oscillations modulate local fast oscillations, usually their amplitude (Canolty & Knight, 2010), which happens to be the predominant effect of astrocytes on fast waves (Perea et al, 2016;Sardinha et al, 2017). By regulating fast waves, astrocytes will have an impact on neuronal encoding, because fast rhythms provide temporal reference frames for local and large-scale computations (Hawellek, Wong, & Pesaran, 2016). Dimensionality reduction (below) may reveal specific astrocytic Ca 2+ regimes associated with coincidence detection, oscillations, and brain state transitions.…”
Section: Astrocytes Could Act As Switches In Brain State Transitionsmentioning
confidence: 99%